PNA-mediated efflux inhibition as a therapeutic strategy towards overcoming drug resistance in Mycobacterium smegmatis - Ghosh, Saptarshi; Cotta, Karishma Berta; Hande, Aniket A.; Fernandes, Moneesha; Mehra, Sarika (Microbial Pathogenesis, 2021)
The emergence of antibiotic-resistant strains of Mycobacterium tuberculosis and the decelerating development of new and effective antibiotics has impaired the treatment of tuberculosis (TB). Efflux pump inhibitors (EPIs) have the potential to improve the efficacy of existing anti-TB drugs although with toxicity limitations. Peptide nucleic acids (PNAs), oligonucleotide mimics, by virtue of their high nucleic acid binding specificity have the capability to overcome this drawback. We, therefore, investigated the efflux pump inhibitory properties of a PNA designed against an efflux pump of Mycobacterium smegmatis. LfrA, an efflux pump found in M. smegmatis, is majorly involved in conferring innate drug resistance to this strain and, therefore, was selected as a target for gene silencing via PNA. qRT-PCR and EtBr assays confirmed the EPI activity of the anti-lfrA PNA. On testing the effect of the anti-lfrA PNA on the bactericidal activity of a fluoroquinolone, norfloxacin, we observed that 5 mu M of anti-lfrA PNA in combination with norfloxacin led to an enhanced killing of up to 2.5 log-fold against wild-type and a lab-generated multidrug resistant strain, exemplifying its potential in countering resistance. Improved efficacy was also observed against intra-macrophage mycobacteria, where the drug-PNA combination enhanced bacterial clearance by 1.3 log-fold. Further, no toxicity was observed with PNA concentrations up to 4 times higher than the efficacious anti-lfrA PNA concentration. Thus, PNA, as an adjuvant, presents a novel and viable approach to rejuvenate anti-TB therapeutics.
Keywords: Adjuvant; Antibiotic resistance; Antisense; Efflux pump; Gene silencing; Mycobacteria; Peptide nucleic acid (PNA)